2010
DOI: 10.1002/j.1556-6678.2010.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectory of Counseling in China: Past, Present, and Future Trends

Abstract: This article surveys the past, present, and future trends of counseling in China. Historically, mental health problems were addressed within the family. Currently, psychotherapy from trained practitioners is available on a limited basis, at least in urban settings. The challenge of mental health in China is tremendous, and the efforts to meet that challenge are encouraging. The authors recommend that in the future, prevention and intervention services be offered that are ecosystemic, strengths‐based, and cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…In addition, studies of young adults in the PRC have found a pervasive stigma attached to marital therapy services (Anderson et al, in press), in part, because seeing a mental health professional is more acceptable if the cause is perceived to be out of one's control (as with a hereditary or environmental problem), than for problems such as interpersonal difficulties (Chen & Mak, 2008). While the Chinese traditionally try to handle problems within the family (Lim, Lim, Michael, Cai, & Schock, 2010), it is plausible that increased family instability due to the rising divorce and remarriage rates may lead young adults to seek more formal, professional sources of information to deal with their marital and relationship problems. The current study seeks to add an important piece to the growing literature around marital therapy in China (see Sim & Hu, 2009) by answering the following research questions:…”
Section: Help-seeking In Chinamentioning
confidence: 99%
“…In addition, studies of young adults in the PRC have found a pervasive stigma attached to marital therapy services (Anderson et al, in press), in part, because seeing a mental health professional is more acceptable if the cause is perceived to be out of one's control (as with a hereditary or environmental problem), than for problems such as interpersonal difficulties (Chen & Mak, 2008). While the Chinese traditionally try to handle problems within the family (Lim, Lim, Michael, Cai, & Schock, 2010), it is plausible that increased family instability due to the rising divorce and remarriage rates may lead young adults to seek more formal, professional sources of information to deal with their marital and relationship problems. The current study seeks to add an important piece to the growing literature around marital therapy in China (see Sim & Hu, 2009) by answering the following research questions:…”
Section: Help-seeking In Chinamentioning
confidence: 99%
“…Couples and family therapy training programs may be likely to grow as a result of enthusiasm for such theories. In addition, psychoeducational approaches to treating mental illness and relationships are perceived well in China, and this has meaningful implications for educational forums that address common relationship problems and marital/relationship enrichment (Lim et al, 2010). Given the ecosystemic framework historically and currently associated with the MFT field (Becvar & Becvar, 2008), MFT programs and MFTs in China could be at the cutting-edge of creating and instituting the curriculums used in these psychoeducational forums.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, the government did establish a three-tiered licensing system that requires increasing levels of training and expertise to practice (Lim et al, 2010). This seems to be a start to the standardization of knowledge and practice within the broader mental health field in Mainland China, though it is likely that the average citizen knows little about this credentialing system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese master's level psychology programs usually do not provide counseling training: "China currently has a three-tier national licensing program that dates from 2002... [under] ...the auspices of the Central Department of Labor" [5, p. 5]. Under this system, individuals can be licensed at all three levels; however, a licensed practitioner at level two or level three must complete a government-approve course and the pass the Department of Labor examination [5]. However, "the highly coveted Level One License is reserved primarily for those who have Qualifying doctoral degrees in the fields of education, medicine, or counseling and have worked as a therapist for at least 3 years" [5, p. 6].…”
Section: Cultural Expectations In Graduate Schoolmentioning
confidence: 99%